The Mirror and the Window: The Seduction of Innocence and Gothic Coming of Age in Låt Den Rätte Komma In/Let The Right One In. Issue 1 (1st May 2016) - Howell, Amanda
Abstract : Swedish film Låt Den Rätte Komma In/Let the Right One In turns away from the representations of sexual threat and desire that have long typified – and currently dominate – vampire fiction and film, a significant generic, narrative, and aesthetic shift. Yet, while the film deliberately cuts sex from its story of love between a boy and a vampire, seduction is still key to its representation of vampirism, as the film plays, as is typical of gothic fiction more generally, upon our cultural investments in innocence.